Cell Proportion and Dimension of Sukun (Breadfruit) (Artocarpus communis FORST) Wood “A Potential Multipurpose Tree Species” - Sri Nugroho Marsoem; Harry Feryanto; Hiroyuki Yamamoto (Wood Research Journal, 2013)
Sukun (Artocarpus communis FORST), also known as breadfruit, is a multipurpose tree and is mostly grown in community forest. In an effort to increase the added value of Sukun trees grown in community forest, a study on the cell proportion and dimension of the wood was conducted by using Sukun trees grown on Karangmojo Village, Bantul Regency, Yogyakarta. Samples for the study were taken from pith to bark in the north direction of the stem. Cell proportion as well as fiber dimension were then observed. The properties observed were analyzed by analysis of variance using a Completely Randomized Design. The result shows that the wood was composed of fiber of only 37.91%, while its rays, parenchyma, and vessel are of 26.60%, 23.85% and 11.61% respectively. The wood had a rather long average fiber length that is 1.65 mm and fiber diameter of 42.48 µm, lumen diameter of 37.28 µm and cell-wall thickness of 2.60 µm.